If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -11 = x + -9 Reorder the terms: -11 + 4x = x + -9 Reorder the terms: -11 + 4x = -9 + x Solving -11 + 4x = -9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -11 + 4x + -1x = -9 + x + -1x Combine like terms: 4x + -1x = 3x -11 + 3x = -9 + x + -1x Combine like terms: x + -1x = 0 -11 + 3x = -9 + 0 -11 + 3x = -9 Add '11' to each side of the equation. -11 + 11 + 3x = -9 + 11 Combine like terms: -11 + 11 = 0 0 + 3x = -9 + 11 3x = -9 + 11 Combine like terms: -9 + 11 = 2 3x = 2 Divide each side by '3'. x = 0.6666666667 Simplifying x = 0.6666666667
| 3a+3=54 | | 8(-1+5x)=112 | | 30=9x+y | | x+10-7=4(x+6)-2(3x+3) | | 103-x=2x+6x-7 | | 8w-13w=25 | | 7b^2+-14b+1=0 | | 4x+11=5x-5 | | 4x+8=2x+31+51 | | 12+40=62 | | 3k-1=7x+2 | | 6+2(x+7)=10-3(x-3) | | 40x^2-x+4000=0 | | 5x+11=5x-5 | | 16+8y=48 | | -1+2-(-3)=10 | | -4j=39 | | -34-5x=-12x+64 | | A+2=12 | | 4x+8+2x+3=51 | | -4(x-1)+2x=34+3x | | 7b^2+-14b+7=0 | | -3x-86=-9x+82 | | -7k-2k= | | -6-z=12 | | (4x^2+2)-(2x^2+3)= | | 11x-61=6x+89 | | X^2+4x=44 | | 4(y-4)-8y=20 | | 3(1-7n)= | | r-10=-12 | | x^2+3x=-4(-2x+1)-2 |